The Astrophysics of Emission-Line Stars - Kogure, Tomokazu; Leung, Kam-Ching (Astrophysics and Space Science Library, 2007)
Many types of stars show conspicuous emission lines in their optical spectra. These stars are broadly referred to as emission line stars. Emission line stars are attractive to many people because of their spectacular phenomena and their variability. The Astrophysics of Emission Line Stars offers general information on emission line stars, starting from a brief introduction to stellar astrophysics, and then moving toward a broad overview of emission line stars including early and late type stars as well as pre-main sequence stars. Detailed references have been prepared along with an index for further reading.